The Effect of Village Expenditure Ratio on Village Income in Kota Pari Village, Serdang Bedagai Regency - Oktarini Khamilah Siregar; Vina Arnita; Mustika Tupa Sihombing (International Journal of Economics and Management Sciences, 2024)
The purpose of this study is to analyze the relationship between village expenditure and village income in various sectors such as village governance, village development, community development, and disaster management in Kotabari Village, Serdang Pedagai Regency, over the period of 2015-2022. The findings indicate that while village expenditure in the village government sector plays a role in influencing village income, expenditure in the areas of village development, community development, and disaster management does not have a significant impact on village income in Kotabari Village. To address this, the village government of Kotabari City aims to balance the distribution of village income by allocating no more than 40% of village expenditure to each sector. The government also plans to allocate funds towards community-focused activities, such as village-wide festivals, which aim to promote local small and medium-sized enterprises and introduce their products to a broader market, both within Indonesia and internationally. Furthermore, it is crucial for the Kotabari Village Government to be more strategic and productive in its budgeted expenditure allocation, as this can stimulate an increase in village income, particularly in terms of village-owned revenue, and move the village towards greater independence and financial sustainability.